Comprehension of acoustically degraded emotional prosody in Alzheimer’s disease and primary progressive aphasia - Jessica Jiang; Jeremy C. S. Johnson; Maï-Carmen Requena-Komuro; Elia Benhamou; Harri Sivasathiaseelan; Anthipa Chokesuwattanaskul; Annabel Nelson; Ross Nortley; Rimona S. Weil; Anna Volkmer; Charles R. Marshall; Doris-Eva Bamiou; et al. (Scientific Reports)
Abstract Previous research suggests that emotional prosody perception is impaired in neurodegenerative diseases like Alzheimer’s disease (AD) and primary progressive aphasia (PPA). However, no previous research has investigated emotional prosody perception in these diseases under non-ideal listening conditions. We recruited 18 patients with AD, and 31 with PPA (nine logopenic (lvPPA); 11 nonfluent/agrammatic (nfvPPA) and 11 semantic (svPPA)), together with 24 healthy age-matched individuals. Participants listened to speech stimuli conveying three emotions in clear and noise-vocoded forms and had to identify the emotion being conveyed. We then conducted correlation analyses between task performance and measures of socio-emotional functioning. All patient groups showed significant impairments in identifying clear emotional prosody compared to healthy individuals. These deficits were exacerbated under noise-vocoded conditions, with all patient groups performing significantly worse than healthy individuals and patients with lvPPA performing significantly worse than those with svPPA. Significant correlations with social cognition measures were observed more consistently for noise-vocoded than clear emotional prosody comprehension. These findings open a window on a dimension of real-world emotional communication that has often been overlooked in dementia, with particular relevance to social cognition, and begin to suggest a novel candidate paradigm for investigating and quantifying this systematically.